2015
DOI: 10.4102/ojvr.v82i1.816
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of antimicrobial usage in livestock animals in south-western Nigeria: The need for alternative plans

Abstract: Resistance to antibiotics has continued to increase, placing future animal and human disease management in real danger. The developing countries characterised by widespread indiscriminate antibiotic use and in which ‘third-generation’ antibiotics are not readily available or affordable are the worst affected. A 3-year (2010–2012) retrospective survey of antibiotic usage in livestock production in three selected states of south-western Nigeria was conducted. Data obtained from eight purposively selected license… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 32 publications
15
86
0
Order By: Relevance
“…We found that several patterns of multidrug resistance were reported in the different studies reviewed and confirmed high levels of resistance to various antimicrobials and common chemical agents [76,77,78,79]. mostly used in Nigeria for prophylactic and therapeutic purposes in animals, as well as for the control and management of multiple bacterial pathogens encountered in veterinary and human medical environments [76].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We found that several patterns of multidrug resistance were reported in the different studies reviewed and confirmed high levels of resistance to various antimicrobials and common chemical agents [76,77,78,79]. mostly used in Nigeria for prophylactic and therapeutic purposes in animals, as well as for the control and management of multiple bacterial pathogens encountered in veterinary and human medical environments [76].…”
Section: Discussionmentioning
confidence: 72%
“…All reference drugs tested in the ARS are commonly used in human and food animals in Nigeria [79]. Very high levels of drug residue in goats’ milk (100%) is of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Even though in many African countries it is illegal for any person who is not a registered veterinarian to administer antibiotics, there are no strict control measures, and often farmers purchase and administer a drug without veterinary prescription and supervision (Adesokan et al . ; Mainda et al . ).…”
Section: Antimicrobial Usage In Livestock and Resistance Patterns In mentioning
confidence: 99%
“…The data of different surveys conducted in Nigeria (Adesokan et al . ), Zambia (Mainda et al . ) and South Africa (Eager et al .…”
Section: Antimicrobial Usage In Livestock and Resistance Patterns In mentioning
confidence: 99%
“…The consumption patterns of antibiotics among humans and its use in agriculture, especially in animal husbandry, have been found globally to correlate with the development of AMR (Oduyebo et al 2008;Goossens 2009;Meyer et al 2013;Adesokan et al 2015;Velickovic-Radovanovic et al 2015;Dyar et al 2016). Resistant strains of bacteria have been isolated from food animals, plant source and dairy products in different parts of the world (Brooks et al 2006; (Kariuki et al 2005), and the estimated incidence of community-acquired non-typhi Salmonella was 166/100,000 people per year for children <5 years (Berkley et al 2005a).…”
Section: Extent and Threat Of Antimicrobial Resistance And Its Impactmentioning
confidence: 99%